mRNA Expression of Genes Involves In Intrinsic Apoptotic Pathway During HIV Infection and Therapy and Its Relation In Circulating cd4 T-Lymphocytes - Mahboob, Nabeela; Munshi, Saif Ullah; Tabassum, Shahina (Bangladesh Journal of Medicine, 2022)
Background: CD4 T-lymphocyte apoptosis in Human Immunodeficiency Virus infection may occur due to activation of the intrinsic apoptotic pathway or triggered via death receptors. In this study, the differential expression of the genes involved in the intrinsic apoptotic pathway was investigated on circulating CD4 T-lymphocytes of HIV-infected patients and healthy controls. Methods: The study included 55 HIV patients who were (1) asymptomatic antiretroviral therapy naive, (2) symptomatic antiretroviral therapy naive, and (3) on antiretroviral therapy. As control 20 healthy persons were included. CD4 T-lymphocytes were isolated from blood samples of HIV patients and healthy controls using density gradient centrifugation method and by negative selection from peripheral blood mononuclear cells (using CD4+ T Cell Isolation Kit followed by total RNA extraction and cDNA synthesis. Genes involved in the intrinsic apoptotic pathway of CD4+ T-lymphocyte including BAX, BAK, BIM, MCL-1 and BCL-2, Caspase-3, Caspase-9 and Calpain-1 were selected and analyzed by real-time PCR to detect their expression. The fold changes of gene expression of PLHIV groups were compared with that of healthy controls. Results: Among the genes under study, no significant upregulation in the expression of BAX, BAK, Caspase-3, Calpain-1 and no significant downregulation in BIM, MCL-1 expression was observed with the exception of upregulation of BCL-2 and downregulation of Caspase-9 expression which were statistically significant (p <0.05). None of the studied genes showed any significant correlations between the gene expressions and CD4 T-lymphocyte count. Conclusion: Gene expression of intrinsic apoptotic pathway may not have significant effect on peripheral CD4 T-lymphocytes count in HIV infection and treatment. Bangladesh J Medicine 2022; 33: 176-185